Pengenalan Teknologi Android Game Edukasi Belajar Aksara Sunda untuk Meningkatkan Pengetahuan - Febriansyah, Feggy; R, Nining; Purnamasari, Ade Irma; Nurdiawan, Odi; Anwar, Saeful (JURIKOM (Jurnal Riset Komputer), 2021)
The rapid development of technology covers many fields that are interconnected with each other, especially in the field of education where when a technology is applied, the learning process is not only limited to between teachers and students but students can access learning through various media. The lack of learning systems still use traditional methods, giving the impression of being bored. From the problems that occur causing a lack of knowledge of children about Sundanese script, due to lack of knowledge in recognizing Sundanese script can result in the loss of regional languages in Indonesia because there are too many elements of language and culture from outside. By making Sundanese script educational games using the ADDIE method, in order to introduce new technology to recognize Sundanese characters. An Android-based educational game that can be used anywhere and anytime and eliminates boredom during the learning process. The results of the research evaluation with the whitebox and blackbox testing process. Whitebox testing is carried out for game use paths, in the blackbox testing process it meets the requirements where tools, buttons can work well. The results of processing the questionnaire data obtained the percentage of attitude toward behavior (X1) of 87%, subjective norms (X2) of 89%, behavioral intention (X3) of 94%, and behavior (Y1) of 91% of the 30 respondents. From this percentage, it can be concluded that this application is able to increase student interest in learning so that it can increase the knowledge of students at SMPN 7 Cirebon City.